Dielectric properties of Bi0.2K0.8(Zn 0.1Ti0.1)Ta0.8O3 ceramics - Piyachon Ketsuwan (2018)
The Bi0.2K0.8(Zn0.1Ti0.1) Ta0.8O3 and Li doped ceramics prepared via the solid-state reaction technique were investigated. The XRD patterns show the single phase cubic perovskite structure without any evidence of secondary phases when sintered at 1250 °C for undoped Bi0.2K0.8(Zn 0.1Ti0.1)Ta0.8O3 and sintered at 1100 °C for Li doped one. The dielectric properties indicate the diffused phase transition (DPT). The dielectric loss of undoped ceramic increases with increasing frequency in temperature range 270 °C down to -150 °C, which suggests low temperature relaxation, while the dielectric loss of Li doped ceramic reveals the interesting lower value over a wide temperature range of about 0 - 300 °C. © (2010) Trans Tech Publications.